Self-consistent simulation studies on effect of methane concentration on microwave assisted H2-CH4 plasma at low pressure. (7th August 2017) - Prasanna, Swaminathan; Michau, Armelle; Rond, Cathy; Hassouni, Khaled; Gicquel, Alix
Abstract: Self-consistent simulations of low-pressure hydrogen-methane plasmas in a microwave-resonating chamber have been conducted. The dynamics of the plasma are dictated by the dominant ion species in the reactor, which is affected by the methane chemistry. Even small concentrations of methane have substantial effects on the plasma, and self-consistent simulations are necessary to capture the wave plasma interaction. In particular, the input power at which the transition between two different coupling regimes, namely a stable single plasma ball regime and a two ball unstable and undesirable plasma regime, takes place depending on the methane composition. The first experimental results show good agreement with the simulations.